SIRI’ DALAM ELONG MASYARAKAT BUGIS DI DAERAH TAWAU, SABAH: ‘SIRI’’ IN THE ORAL TRADITION OF BUGINESE ‘ELONG’ IN TAWAU, SABAH - Tanra, Mansur; Amat Amat, Asmiaty (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract The Bugis people, originally from Sulawesi, has moved to and enhanced multiculturalism in Sabah. They gather in communities that retain many ancestral traditions despite inhabiting faraway lands. They are proud of inheriting their local Buginese wisdom, preserved and well-protected, especially by elders. This wisdom is passed on to subsequent generations to be practised – even in modern times. One such wisdom is called ‘siri’’ which represents pride and dignity upon which they build their lives. Therefore, this paper aimed to identify values reflecting ‘siri’’ in the Buginese ‘elong’ using Paul Ricoeur’s Hermeneutic approach. ‘Elong’ or words were obtained through interviews conducted on informants aged 50 and above in the Buginese community during a field study at Tawau. Findings showed a few themes within the ‘elong’, such as making a living, knowing the importance of knowledge, having good manners, preserving dignity and forgiving. The examination of ‘elong’ proved that they contain ‘siri’’ to steer the Buginese living within various communities. Keywords: Siri’, Elong, the Bugis, Paul Ricoeur’s Hermeneutics.